Antigenic cross reactivity between the pneumococcal polysaccharide vaccine and the streptococcus pneumoniae 7f one of the prevalent sertypes in Bangladesh - Shahriar, Mohammad (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2008.